Reporting of Endangered Animals at Tourist Destination Locations using Self-Reporting Applications - WIJAYA, Marvin Chandra (Journal of Environmental Management and Tourism; Vol 13 No 7 (2022): JEMT, Volume XIII, Issue 7(63), Winter 2022DO - 10.14505/jemt.v13.7(63).21, 2022)
Many tourist destinations in Indonesia are nature reserves, forests, beaches, and other natural attractions. In these tourist destinations, there are usually endangered species. Meanwhile, the Center for Nature Conservation in Indonesia requires mapping data for endangered animals. Mapping is costly and time-consuming. In this study, a system that involves tourists in mapping endangered animals is proposed. Application was developed to create an endangered animal reporting system. This application can be used on Android-based smartphones. This application has four features: Event, Gallery, Report, and Message. This application also has an educational function about endangered animals. Overall this application is rated positively by its users (tourists and tourist destination management). This app is rated 4.5 (Likert scale) by tourists and rated 4.2 by tourist destination managers. Photographs of endangered animals reported by tourists managed to process and map endangered animals.